1994
DOI: 10.1210/endo.134.6.7515004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of K+ and Ca2+ ionic currents in glomerulosa cells from human adrenal glands.

Abstract: Ionic currents of primary cultured glomerulosa cells from human adrenal glands were studied with the patch-clamp technique. Two types of outward K+ currents and two types of inward Ca2+ currents were described. The transient outward K+ current activated at potential positive to -40 mV and demonstrated a marked time-dependent inactivation. It was blocked by 4-aminopyridine but not tetraethylammonium. A second type of outward current activated rapidly at the depolarization onset and then increased slowly with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…We have previously shown that, in human glomerulosa cells, NiCl 2 and nifedipine specifically blocked Ca 2ϩ channels (22). Results from Fig.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…We have previously shown that, in human glomerulosa cells, NiCl 2 and nifedipine specifically blocked Ca 2ϩ channels (22). Results from Fig.…”
Section: Resultsmentioning
confidence: 66%
“…As previously described by our group, human glomerulosa possess both K ϩ and Ca 2ϩ currents (22). T-and L-type Ca 2ϩ currents were studied after blocking outward currents and using a double pulse protocol as described previously (22).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such observations could explain that, in humans, aldosterone secretion is more sensitive to low doses of ACTH(1-24) than the secretion of cortisol or DHEA (Daidoh et al 1995), especially in conditions of sodium depletion (Rayfield et al 1973, Kem et al 1975, Nicholls et al 1975. In rat and human ZG cells, binding of ACTH to its receptor induces a rapid membrane depolarization, in part due to blockade of K + channels (Payet et al 1987(Payet et al , 1994. Simultaneously, depolarization transiently abolishes T-channel activity (Durroux et al 1991) and increases the amplitude of the L-type current, through a cAMP-dependent or a PKA-dependent phosphorylation of these L-type channels (Durroux et al 1991).…”
Section: Effects Of Acth On Electrical Properties Of Adrenocortical Cmentioning
confidence: 99%